In memoriam: akadeemik Raimond Hagelberg. Zusammenfassung: Akademiker, Professor Raimond Hagelberg. In Memoriam - Sõrg, Mart (Estonian Discussions on Economic Policy, 2013)
Raimund Hagelberg has secured an essential place in the history of Estonian economy as a precious university lecturer, scientist, advisor and coordinator. He was a hard working man, who, for more than half of a century, was very thorough in everything he did. By doing that, duties and tasks themselves automatically looked for him and found him as well.After graduating from the Tallinn Polytechnical Institute (now Tallinn University ofTechnology) in 1950 in the field of finance and credit, he undertook the postgraduate course and in 1954 successfully defended his Ph.D. thesis on the topic of crediting agricultural farms. After the post-graduate course he was appointed to work in the Institute of Economics of Academy of Sciences Estonian SSR. But very soon afterwards, during the same year in fact, he was relocated to Tartu State University in order to re-establish the Faculty of Economics and the speciality of finance and credit in this faculty.Raimund Hagelberg’s job in Tartu lasted for nearly 30 years, he has called the University of Tartu as his second home. During this period in Tartu he advanced from the post of senior lecturer to the status of assistant professor (1958) and from 1968 onward he started to work as a full professor. In 1967 he defended his doctoral thesis "The Basics of the Analysis of the Business of Agricultural Enterprises". This work was also published as a textbook and students and practitioners of agricultural farms used it for introducing scientific methods in the analysis of the agricultural sector.His scientific production was on the five fields of economic sciences. These were: economic analysis methodology and methods; theory of finance and corporate finance; education and the economics of higher education; economics theory and finally, researches in the field of money, banking and credit matters. In 2002, Raimund Hagelberg calculated that he was the author or co-author of 11 monographs, one textbook, and 133 scientific papers. In addition, he had published numerous articles in Estonian press.In 1981 Raimund Hagelberg became a academian at the Academy of Sciences of Estonian SSR and a year later as a Secretary General of this Academy. He worked at this post for seven years until his retirement. However, after only half of the year he was called back to work, this time as the advisor in the team of the Chairman of the Presidium of the Supreme Council of Estonian SSR. In 1990 he was elected as a member to the Board of reopened central bank – Bank of Estonia. He worked there for 8 years as a board member and after continuously as advised the Bank of Estonia. It was during this period from 1990, which he identified as the final spurt in his career, and in his opinion, it was then that he sought to do much more for Estonia than he had before.Professor Raimund Hagelberg was an honoured scientist of Estonia from 1979 onwards. In 1995 he was awarded the status of Professor Emeritus of University of Tartu and in 2000 he was decorated with the Order of National Coat of Arms. He passed away last year but he is still surviving amongst us in the course of his works and through all of his almost one and a half thousand students